Histone and non-histone lactylation: molecular mechanisms, biological functions, diseases, and therapeutic targets - Xia Peng; Juan Du (Molecular Biomedicine)
Abstract Lysine lactylation (Kla) is a recently discovered post‑translational modification in which a lactyl moiety is transferred onto the ε‑amino group of lysine residues, linking cellular metabolism to epigenetic and signaling pathways. This process is regulated by a range of enzymes and metabolites, including lactate, “lactyltransferases (writers)”, “Delactylases (erasers)”, and “readers” involved in the modification. Histone lactylation has been observed in H2A, H2B, H3, and H4, with H3K18la and H4K12la being the most extensively studied sites, linked to numerous biological functions. Beyond chromatin, Kla has also been identified in a growing number of non-histone proteins, further expanding its functional significance. For instance, non-histone proteins such as AARS1-K120la, ACSS2-Kla, MRE11-K673la, NBS1-K388la and GNAT13-Kla has illuminated novel regulatory mechanisms and reinforced the potential of non-histone Kla as a promising avenue for research. Importantly, aberrant Kla patterns have been linked to various disease states, including cancer, inflammation, and metabolic disorders, highlighting its emerging potential as a biomarker and therapeutic target. In this review, we systematically summarize the molecular mechanisms, biological functions, disease associations, and therapeutic implications of both histone and non-histone Kla. By integrating current findings and discussing existing challenges, we aim to provide a comprehensive overview that will deepen understanding of Kla biology and inspire future research into its diagnostic and therapeutic potential.